Resilient community : transforming abandoned residence blocks of Sungai Pari Towers, Ipoh as catalyst to local community - Salleh, Nur Hafizah (2018)
Marginalized community has been neglected in the community itself. They have been denied involvement in mainstream economic, political, cultural and social activities. These groups need a space where they can interact with difference community. Through community building, they can create and enhance one community in a neighbourhood to achieve a common good closure. They need a proper space in order to enjoy a harmonious and safe living. A quality and practical building plays an important role to create a society that is always engage and interact with each other. The study focused on the suburb area in Ipoh, which is Buntong. The study emphasizes the spaces that are being neglected by the community and gives a negative effect to the surrounding. A detailed study on social demographic, circulation and land use of Buntong area are provided for design solution. With this study, we are able to find out the problems exist and make planning guidelines and design space quality, which can meet the needs of users as well as create a good community living in this area.